A new domain model for estimating water distribution in soil pores during the drying and wetting processes - Zhai, Qian (2023)
It is well known that both the soil-water characteristic curve (SWCC) and hydraulic conductivity function (HCF) of unsaturated soils are hysteretic. Modeling the hysteresis behavior of unsaturated soil is crucial for understanding the hydraulic properties of unsaturated soil and solving geotechnical problems in practice. There have been two types of models, the empirical model and the domain model, proposed to describe SWCC hysteresis. The results from the empirical model are subject to the model parameters, and the domain model has a physical theoretical background. However, the application of the domain model requires calibration using experimental data. In this technical note, a new domain model is proposed for estimating the water distribution in soil during both the drying and wetting processes. Consequently, the main wetting curve and the drying scanning curve can be estimated using the proposed domain model in this study. The estimated results from the proposed model agree well with the experimental data (a total of 16 sets) from different studies. The method proposed in this technical note provides a reliable approach for estimating water distribution in pores with different sizes for various types of soil.